Physiological Signal Analysis for Evaluating Flow during Playing of Computer Games of Varying Difficulty - Tian, Yu; Bian, Yulong; Han, Piguo; Wang, Peng; Gao, Fengqiang; Chen, Yingmin (Frontiers in Psychology, 2017)
Flow is the experience of effortless attention, reduced self-consciousness, and a deep sense of control that typically occurs during the optimal performance of challenging tasks. On the basis of the person–artifact–task model, we selected computer games (tasks) that have different levels of difficulty (difficult, medium, and easy) and shyness (personality) as flow precursors for studying the physiological activities that occur during the flow state. Cardiac and respiratory activities and the average changes of skin conductance were measured continuously during the participants’ (N = 40) performance. Moreover, the associations between self-reported psychological flow and physiological measures were investigated using a series of repeated-measures analyses. The results showed that flow experience are related to faster respiratory rate, deeper respiratory depth, moderate heart rate, moderate heart rate variability, and moderate skin conductance. The main effect of shyness was not significant, whereas the interaction between shyness and difficulty influenced flow experience. These findings are discussed in relation to current models of arousal and valence. It is proposed that flow is a state of moderate mental effort that arises through the increased parasympathetic modulation of sympathetic activity.